KUANTITAS PENDONOR DARAH BERDASARKAN JENIS KELAMIN DAN GOLONGAN DARAH PADA BULAN JANUARI TAHUN 2023 DI UDD PMI KOTA SEMARANG - Khalidah, Ummu; Puspita, Rina; Ariani, Resti (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2024)
Voluntary blood donor (DDS) is someone who donates blood voluntarily without coercion for the benefit of people in need without knowing who the blood is for. The purpose of this study was to describe the results of donors and the characteristics of blood donors at UDD PMI Semarang City in January 2023. The method used in this study was a quantitative descriptive study, at UDD PMI Semarang City in January 2023 based on secondary data from Simdondar. The results of the study showed that the number of successful blood donors at UDD PMI Semarang City was 3,330 donors. The results of the study showed that the majority of blood donors were blood group O, namely 1,299 donors (39.01%), and the least blood type AB was 274 (8.22%). The majority of donors were male, namely 2,409 (72.34%), for women 321 (27.66%). The conclusion of this study is that the results of an analysis of donor characteristics at UDD PMI Semarang City can be used as basic information for optimizing blood supply management.